Analisis Faktor-Faktor Preferensi Mahasiswa terhadap Perbankan Syariah - Ayif Fathurrahman; Umi Azizah (Universitas Ahmad Dahlan, 2019)
This research proposed to determine the factors of customer preferences in Islamic or Sharia banking. The research sampling which being use is the students of Economic studies mainly in 5th semester and 7th semester. The research designed in quantitative research by collecting data using questionnaires. Analysis technique using doubled linear regression. The result indicates that (1) Religion or beliefs have positive effect towards the rate of Economic Studies students preferences in Muhammadiyah Yogyakarta University towards Sharia Banking; (2) Costs factor has adverse effect but further insignificant towards the level of Economic Studies students preferences in Muhammadiyah Yogyakarta University towards Sharia Banking; (3) Benefits factor has positive effect yet negligible to the level of Economic Studies students preferences in Muhammadiyah Yogyakarta University towards Sharia Banking; (4) Facilities factor carry out positive impact towards the rate of Economic Studies students preferences in Muhammadiyah Yogyakarta University towards Sharia Banking; (5) Knowledge factor positively affected towards the rate of Economic Studies students preferences in Muhammadiyah Yogyakarta University towards Sharia Banking.